Estudo da influência do fator água/cimento na confecção de compósitos cimentícios com argila expandida e seus impactos na microestrutura - Souto, Bremmer Carneiro Cavalcante (2022)
Civil construction is considered of fundamental importance for the development of the world economy, responsible for the creation of essential products and services, in addition to contributing to the generation of jobs. The built environment has required increasingly advanced materials with specific performance characteristics. Within this scope, concrete and mortars play a fundamental role in the production of various elements of civil construction. Therefore, the present study aims to evaluate the effect of the variation of the water/cement (w/c) ratio for the manufacture of lightweight cementitious composites, with total replacement of the natural aggregate by expanded clay, and to analyze its mechanical performance correlating with the microstructure. After characterizing the aggregate, 16 specimens were made, in the proportion (mix design) 1:6 (CP V cement - ARI: 2.50 mm expanded clay), with 5.0 cm in diameter and 10 cm in height, varying the water/cement ratio: T1 (w/c 0.5), T2 (w/c 1.0), T3 (w/c 1.2), T4 (w/c 1.3) and T5 (w/c 1.3) c 1.5). An axial compressive strength test was performed at 7, 14, 21 and 28 days, using a hydraulic press. The composite density at 28 days, efficiency factor and capillary absorption were determined. With the scanning electron microscope (SEM) information about the morphology, distribution and porosity of the composites was obtained. The results obtained in the tests of physical characterization of the composite qualify it as a light cementitious composite; it was observed, in general, that the compressive strength of all traces reached about 80% of the final strength, at 7 days; the high porosity of the composite was confirmed by the absorption of water in the first hours of testing and, later, by the Scanning Electron Microscopy test. As it presents the best efficiency factor and the lowest water absorption, the T2 mix with a w/c ratio = 1.2 can be considered the most suitable for the development of constructive elements (block, plate, tile), which satisfy, for example, the requirements of NBR 15575. In general, with the reach of the mechanical indexes recommended in the standard, it is possible to observe the technical feasibility for the application of this material in buildings, aiming to take advantage of its qualities as a contribution to reducing loads on the structures of the buildings, in addition to thermoacoustic insulation.